The relationship between workplace environments and job performance in selected government offices in Selangor, Malaysia / Nur Zainie Abd Hamid and Narehan Hassan - Abd Hamid, Nur Zainie; Hassan, Nur Zainie (2014)
Work ethics among employees has been extensively studied since it is believed to influence job performance. One of the elements of work ethics is the workplace environments that may represent job satisfaction, organizational factors and clients. Research evidences showed that, the element plays a vital role in producing positive employees. This has become the reason for employers to be champions in mastering all the important factors that lead to an employee’s high performance, especially those in the government sector where job performance is a crucial issue to be discussed. Thus, the purpose of this study is to examine the relationship between workplace environments and civil servants’ job performance in Shah Alam, Selangor. This survey based correlation study using a simple random sampling technique where 150 respondents are selected from 10 government offices. Questionnaires were personally distributed with 100 percent rate of return. The data gathered is analyzed using Statistical Package for Social Science (SPSS) through descriptive statistic and Pearson Product Moment Correlation test. The findings found that two major elements in the workplace; workplace environment and job performance have a weak association. The finding of this study is very critical since it can help the employers in improving the worker satisfaction especially through adjusting the workplace environments in which as a result will increase the level of their job performance.